Twinkle Megane: Evaluation of Near-Eye LED Indicators on Glasses for Simple and Smart Navigation in Daily Life - Firouzian, Aryan; Kashimoto, Yukitoshi; Yamamoto, Goshiro; Keranen, Niina; Asghar, Zeeshan; Pulli, Petri (EAI Endorsed Transactions on Pervasive Health and Technology, 2017)
We present an eyeglass-type wearable device that has light emitting diode (LED) indicators on the frame. The device produces lighting patterns of 14 RGB LEDs near user’s eyes as guiding information. Since installed LEDs are light and saving power, it is feasible to develop it for daily use. On the other hand, it cannot provide rich information such as text or images. In this study, we aim to realize a remote assistive system that provides assistive commands by visual cues from remote sites. Especially, we consider elderlies who are suering from mild cognitive impairment as users. They would be one of potential user groups since the device does not block their sights by text or images and it can be worn in daily life without the additional sense of restraint. This paper explains our conceptual assistive system structure, a prototype eyeglass-type device with near-eye LED indicators and usability experimentation in simple detecting and walking navigational tasks.
Keywords: Head Mounted Display; wearable device; LED indicators; assistive system; elderly; mild cognitive impairment